PENGEMBANGAN LAYANAN PERPUSTAKAAN BAGI PEMUSTAKA DIFABEL DI PERPUSTAKAAN UIN SUNAN KALIJAGA - Isrowiyanti, Isrowiyanti (Pustakaloka, 2014)
Abstract: The dissable (difabel) students are a part of academic society that have rights to access information resources and library services. This paper tries to describe UIN Sunan Kalijaga Libraryâs efort to provide some adaptive tools and an atmosphere supporting for the dissable or students accessiblility. This article shows that managers of this institution support policies in favour of the dissable in the university, and this experience could be implemented inÂ  other libraries.Â Keyword: library services, difabel, accessibility